Pengaruh PAD, PMA dan Inflasi terhadap Pertumbuhan Ekonomi Provinsi Bali - Dewi, Sakita Laksmi; Purbadharmaja, Ida Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 11, November 2013 (pp. 492-546), 2013)
The aim of this research is to determine the direct and indirect effect of regional income, foreign capital and inflation of Bali economic growth. This research uses cross section data using time period in 2012, data processing using the method Bootstrapping  using the technique of  path analysis with the LISREL program. The analysis founds that the variable indirectly regional income not significantly affect economic growth through foreign capital, variable inflation indirectly was not significantly affect economic growth through foreign capital, variables directly regional income significantly affect economic growth, foreign capital are not significantly effect for regional economic growth. and inflation variables are not significantly  effect for economic growth.
Keywords: economic growth , regional income , foreign capital , inflation